Changes in benzoic acid content of goat milk kefir produced using different kefir cultures - Şendoğan, Gizem (Array, 2020)
In this study, the content of hippuric and benzoic acid of goat milk kefir produced with commercial lyophilized kefir cultures and kefir grain was investigated. 9 commercial kefir culture and 1 kefir grain were used in production of goat milk kefir. Based on the obtained results, hippuric acid was not found in kefir samples during the storage period, whereas goat milk samples contained hippuric acid (14.8 mg/kg). Benzoic acid levels of kefir samples ranged from 8.5 to 26.6 mg/kg during the 28-day storage period. The highest Lactobacillus and Lactococcus counts were observed in kefir sample produced with kefir grain while this sample was one of the sample containing the lowest (11.2 mg/kg) benzoic acid levels.